Education and mobility - Stephen Machin; Panu Pelkonen; Kjell G. Salvanes (Institute for the Study of Labor (IZA), 2008)
We show that the length of compulsory education has a causal impact on regional labour mobility. The analysis is based on a quasi-exogenous staged Norwegian school reform, and register data on the whole population. Based on the results, we conclude that part of the US-Europe difference, as well as the European North-South difference in labour mobility, is likely to be due to differences in levels of education in the respective regions.
urn:nbn:de:101:1-2008120247
Keywords: I28; 330; Education; mobility; labour market; Allgemeinbildende Schule; Dauer; Arbeitsmobilität; Korrelation; Norwegen